Representation of Ideals through Symbols in the Novel Al-Arnab fī al-Qamar - Sharifa, Khiliatus (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to analyze the representation of aspirations through the use of symbols in the Novel Al-Arnab fī al-Qamar. This study is important because symbols in literary works are often used by authors to convey ideas, hopes, and the inner experiences of characters indirectly. This research employs a descriptive qualitative method with a semiotic approach to examine the meanings of symbols found in the text. The data consist of excerpts from the story containing symbolic elements. Data collection techniques were carried out through library research and in-depth reading (close reading), while data analysis was conducted by identifying symbols, examining their relationship with the story’s context, and interpreting the meanings embedded within them. The results show that symbols in the story Al-Arnab fī al-Qamar, such as the rabbit and the moon, represent aspirations, hopes, and the character’s efforts to achieve life goals. These symbols illustrate the dynamics between human limitations and the desire to transcend them. Thus, the use of symbols in this story demonstrates that literary works can serve as a medium for reflecting on human aspirations and provide a deeper understanding of the meaning of life.